Meiotic Crossing Over in Maize Knob Heterochromatin. Issue 3 (1st March 2017) - Stack, Stephen M; Shearer, Lindsay A; Lohmiller, Leslie; Anderson, Lorinda K
Abstract: There is ample evidence that crossing over is suppressed in heterochromatin associated with centromeres and nucleolus organizers (NORs). This... There is ample evidence that crossing over is suppressed in heterochromatin associated with centromeres and nucleolus organizers (NORs). This characteristic has been attributed to all heterochromatin, but the generalization may not be justified. To investigate the relationship of crossing over to heterochromatin that is not associated with centromeres or NORs, we used a combination of fluorescence in situ hybridization of the maize 180-bp knob repeat to show the locations of knob heterochromatin and fluorescent immunolocalization of MLH1 protein and AFD1 protein to show the locations of MLH1 foci on maize synaptonemal complexes (SCs, pachytene chromosomes). MLH1 foci correspond to the location of recombination nodules (RNs) that mark sites of crossing over. We found that MLH1 foci occur at similar frequencies per unit length of SC in interstitial knobs and in the 1 µm segments of SC in euchromatin immediately to either side of interstitial knobs. These results indicate not only that crossing over occurs within knob heterochromatin, but also that crossing over is not suppressed in the context of SC length in maize knobs. However, because there is more DNA per unit length of SC in knobs compared to euchromatin, crossing over is suppressed (but not eliminated) in knobs in the context of DNA length compared to adjacent euchromatin.